Development of Youth Soft Skill in Organizations Through Basic Public Speaking Training - Entoh Tohani; Diyas Dwi Lestari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Humans are social creatures who cannot live individually, but humans need the help of others. In interacting, both with themselves and with other people, personally and in groups, humans need to communicate. Everyone can communicate both verbally and non-verbally, but not everyone is able to communicate in public. Public speaking skills are important for everyone from any background to learn. The development of youth soft skills in organizing through basic public speaking training is one way to improve speaking skills in organizations and train youth to be confident. The method used in this research is observation and interviews. This activity can develop and improve youth skills in public speaking so that teenagers can be more confident. After this training, Karang Taruna (Youth Organization) of Putat 1 Village members can be more active and participate in discussions. Teenagers become more confident in expressing their opinions and are able to make the organization better.